Striking a balance : improving practice as a student doing group music therapy with adults with substance abuse and dependence : a research thesis presented in partial fulfilment of the requirements for the Master of Music Therapy at the New Zealand School of Music, Wellington, New Zealand - Yearsley, Sharon (Massey University, 2010)
An action research project was devised to help a music therapy student improve her practice in a group alcohol and drug treatment setting. The project initially focussed on improving practice by delivering more creative, sustained and holistic experiences. Four action cycles of one week each were carried out, each cycle comprising planning, action and reflection stages. Data sources were gathered in the form of clinical notes, a reflective journal and supervision notes from meetings and session de-briefs with counselling staff at the facility. The data was then woven into narrative accounts of each cycle, and key learning points for each cycle were identified. Cycles were also examined for common themes, and nine themes were identified. Findings show the student developing a deeper understanding of practice through the examination of structure and flexibility in facilitation style and musical interactions, and how and when to find balance between structure and freedom. Other key factors relevant to improving practice such as building confidence and working with the interdisciplinary team, are explored. Findings are discussed, along with ideas about the value of carrying out an Action Research project, and suggestions for future projects focussed on improving practice with this client group.
Keywords: Music therapy; Substance abuse; Substance dependence; Action research; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410101 Music studies